Anti-corrosion thermal control bifunctional coating on magnesium alloy surface and preparation method of anti-corrosion thermal control bifunctional coating

By forming a magnesium-zinc layered bimetallic hydroxide anti-corrosion coating on the surface of the magnesium alloy and preparing an inorganic thermal control coating and transition layer on it, the problem of difficulty in preparing a low solar absorption specific thermal control coating on the surface of the magnesium alloy is solved, and high-performance anti-corrosion and thermal control dual functions are achieved, which is suitable for the aerospace field.

CN119753659APending Publication Date: 2025-04-04SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411778244.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

It is difficult to prepare high-performance thermally controlled coatings with low solar absorption ratio on the surface of magnesium alloys, which limits the widespread application of magnesium alloys in spacecraft.

Method used

Magnesium-zinc layered bimetallic hydroxide is used as the anti-corrosion coating, and an inorganic thermal control coating and transition layer are prepared on its surface. The binding force and thermal control performance of the coating are improved through ionic replacement and chemical bonding.

Benefits of technology

It realizes a high-performance anti-corrosion and thermal control dual-function coating on the surface of magnesium alloy, with good space environment stability and low solar absorption ratio, and is suitable for the aerospace field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753659A_ABST
    Figure CN119753659A_ABST
Patent Text Reader

Abstract

The invention relates to an anti-corrosion thermal control bifunctional coating on the surface of a magnesium alloy and a preparation method of the anti-corrosion thermal control bifunctional coating. The anti-corrosion and thermal control dual-function coating on the magnesium alloy surface comprises a magnesium-zinc alloy matrix, an anti-corrosion coating formed on the surface of the magnesium-zinc alloy matrix in situ and a thermal control coating distributed on the surface of the anti-corrosion coating in a dispersed mode. Preferably, the anti-corrosion coating is a magnesium-zinc layered double metal hydroxide coating; and the thermal control coating is an inorganic thermal control coating. The anti-corrosion and thermal control bifunctional coating on the surface of the magnesium alloy has good anti-corrosion performance and thermal control function, and can be applied to the field of spaceflight.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material preparation, and relates to an anti-corrosion and thermal control dual-function coating on the surface of a magnesium alloy and a preparation method thereof, and specifically relates to an anti-corrosion and thermal control dual-function coating on the surface of a ZK61M magnesium-zinc alloy and a preparation method thereof. Background Art

[0002] In the aerospace field, the amount and location of magnesium alloys are increasing day by day. However, due to the corrosion-prone nature of magnesium alloys, it is still difficult to prepare high-performance inorganic white thermal control coatings on their surfaces, which limits the widespread application of magnesium alloys in spacecraft and seriously affects the thermal control design of high-performance spacecraft.

[0003] At present, the preparation method of thermal control coating on the surface of magnesium alloy is mainly electrochemical anodization or micro-arc oxidation process, which is determined by the active chemical properties of magnesium alloy. Electrochemical anodization or micro-arc oxidation process can grow coating in situ on the surface of magnesium alloy, which can completely cover the surface of magnesium alloy and prevent oxidation corrosion of magnesium alloy due to storage. However, the solar absorption ratio of thermal control coating of magnesium alloy prepared by electrochemical anodization or micro-arc oxidation process can only reach 0.32 at the lowest, and it is impossible to prepare thermal control coating with lower solar absorption ratio. Summary of the invention

[0004] In order to solve the problem of preparing thermal control coating with low solar absorption ratio on the surface of magnesium-zinc alloy (such as ZK61M (Zn content is 5.43%)), the present invention provides a corrosion-resistant thermal control dual-function coating on the surface of magnesium alloy and a preparation method thereof.

[0005] In the first aspect, the present invention provides an anti-corrosion and thermal control dual-function coating on the surface of a magnesium alloy, comprising: a magnesium-zinc alloy substrate, an anti-corrosion coating formed in situ on the surface of the magnesium-zinc alloy substrate, and a thermal control coating dispersed on the surface of the anti-corrosion coating; preferably, the anti-corrosion coating is a magnesium-zinc layered double metal hydroxide coating; and the thermal control coating is an inorganic thermal control coating.

[0006] Inorganic thermal control coatings have good stability in space environments and are the preferred thermal control coating materials for long-life spacecraft. However, the bonding strength between inorganic thermal control coatings and substrates is usually poor, and it is impossible to directly prepare inorganic thermal control coatings on substrates to improve the thermal control performance of substrates. Therefore, the present invention selects a magnesium-zinc layered double hydroxide coating with a layered structure as an anti-corrosion coating. Its unique ion replacement advantage can effectively improve the bonding strength with the inorganic thermal control coating. In addition, the present invention can further enhance the bonding strength between the anti-corrosion coating and the inorganic thermal control coating by preparing a transition layer on the surface of the anti-corrosion coating.

[0007] Preferably, the Zn content in the magnesium-zinc alloy matrix is ​​2-9 mol%, and the balance is Mg.

[0008] Preferably, the inorganic thermal control coating is at least one of a silicate coating, a phosphate coating, a silica sol coating, and an oxide coating.

[0009] Preferably, the surface of the anti-corrosion coating also includes a transition layer; preferably, the transition layer is at least one of a silicate solution coating, a phosphate solution coating, a silica sol coating, an acrylic emulsion coating, a tetraethyl orthosilicate coating, and a silane solution coating.

[0010] Preferably, the thickness of the anti-corrosion and thermal control dual-function coating is 100-200 μm.

[0011] Preferably, the corrosion potential of the anti-corrosion and thermal control dual-function coating is greater than -1.4645 eV.

[0012] In a second aspect, the present invention provides a method for preparing an anti-corrosion and thermal control dual-function coating on a magnesium alloy surface, comprising: (1) forming an anti-corrosion coating of magnesium-zinc layered double hydroxide in situ on the surface of magnesium-zinc alloy substrate; (2) Spraying a thermal control coating on the magnesium-zinc layered double metal hydroxide anti-corrosion coating, and drying the coating to obtain an anti-corrosion and thermal control dual-function coating on the surface of the magnesium alloy.

[0013] Preferably, in step (1), the method for preparing the magnesium-zinc layered double metal hydroxide anti-corrosion coating comprises: placing a magnesium alloy substrate in a carbonate solution for a first immersion treatment; then, adding an alkaline solution thereto or transferring the magnesium alloy substrate after the first immersion treatment to an alkaline solution for a second immersion treatment; and drying the magnesium alloy substrate after the second immersion treatment to obtain a magnesium-zinc layered double metal hydroxide anti-corrosion coating.

[0014] Preferably, the concentration of the carbonate solution is greater than 0.02 mol / L, and the pH is not higher than 5.0; preferably, the pH is 3.8 to 4.2; The preparation process of the carbonate solution is: heating deionized water to 40-60° C., and then continuously introducing CO 2 gas to obtain a carbonate solution; preferably, the flow rate of the introduced CO 2 gas is 0.5-1.5 L / min.

[0015] Preferably, the first immersion treatment is carried out under normal pressure; the temperature of the first immersion treatment is 20-50°C, preferably 50°C; the time of the first immersion treatment is more than 1 hour, preferably 1-4 hours, most preferably 1-2 hours.

[0016] Preferably, the composition of the alkaline solution includes at least one of NaOH, KOH, LiOH, NH4OH, Ca(OH)2, Ba(OH)2, Sr(OH)2, CsOH, and FrOH; The pH value of the mixed solution after the alkaline solution is added dropwise and the pH value of the alkaline solution is greater than 8, preferably 9-12, and most preferably 10-11.

[0017] Preferably, the second immersion is carried out under normal pressure; the temperature of the second immersion is 30-90°C, preferably 90°C; the time of the second immersion is more than 1 hour, preferably 2-8 hours, most preferably 3-4 hours.

[0018] Preferably, the drying temperature is 40-60°C, preferably 50°C; and the drying time is not less than 1 hour.

[0019] Preferably, the preparation method also includes: before spraying the thermal control coating on the magnesium-zinc layered double hydroxide anti-corrosion coating, spraying a transition layer solution on the magnesium-zinc layered double hydroxide anti-corrosion coating, and after drying, obtaining a transition layer on the surface of the magnesium-zinc layered double hydroxide anti-corrosion coating.

[0020] Preferably, the transition layer solution is at least one of a silicate solution, a phosphate solution, a silica sol, an acrylic emulsion, tetraethyl orthosilicate, and a silane solution; preferably, the transition layer solution is at least one of a K2SiO4 solution, tetraethyl orthosilicate, an acrylic emulsion, and 3-aminopropyltriethoxysilane; the mass percentage concentration of the transition layer solution is 10% to 50%.

[0021] Preferably, in the process of preparing the transition layer, the drying temperature is 30 to 120° C. and the drying time is 1 to 24 hours.

[0022] Preferably, in step (2), the raw material composition of the thermal control coating is a mixture of ZnO powder, K2SiO4 solution and 3-aminopropyltriethoxysilane; preferably, the mass ratio of ZnO powder, K2SiO4 solution and 3-aminopropyltriethoxysilane is 0.1~1:0.1~1:0.1~1.

[0023] Preferably, in step (2), the drying temperature is 30 to 120° C. and the drying time is 0.5 to 12 hours.

[0024] In the present invention, the magnesium-zinc layered double hydroxide anti-corrosion coating provides anti-corrosion capability for the magnesium alloy, the transition layer increases the bonding strength between the anti-corrosion coating and the thermal control coating, and the thermal control coating provides thermal control performance. In addition, the use of ZnO powder to prepare the thermal control coating can further reduce the solar absorption ratio.

[0025] Beneficial effects: (1) The anti-corrosion and thermal control dual-function coating on the surface of the magnesium alloy prepared by the present invention has good anti-corrosion performance and thermal control function, and can be applied in the aerospace field; (2) The preparation method of the anti-corrosion and thermal control dual-function coating provided by the present invention is simple to operate, low in cost, short in time, and easy to promote and apply in engineering. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the anti-corrosion and thermal control dual-function coating; Figure 2 The anti-corrosion and thermal control dual-function coating prepared in Example 1; Figure 3 This is a real picture of the corrosion after the thermal control coating was directly sprayed on the surface of the magnesium-zinc alloy substrate in comparative example 1 (wherein the white part is the coating and the black spots are the corroded parts). DETAILED DESCRIPTION

[0027] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.

[0028] First, the present invention provides a dual-function anti-corrosion and thermal control coating on the surface of a magnesium alloy, comprising: a magnesium-zinc alloy substrate, an anti-corrosion coating formed in situ on the surface of the magnesium-zinc alloy substrate, and a thermal control coating dispersed on the surface of the anti-corrosion coating; preferably, the content of Zn in the magnesium-zinc alloy substrate is 2-9 mol%, and the balance is Mg. The anti-corrosion coating is a magnesium-zinc layered double metal hydroxide coating; the thermal control coating is an inorganic thermal control coating; preferably, the inorganic thermal control coating is at least one of a silicate coating, a phosphate coating, a silica sol coating, and an oxide coating.

[0029] The following is an exemplary description of the method for preparing the anti-corrosion and thermal control dual-function coating on the surface of a magnesium alloy provided by the present invention.

[0030] Pretreatment of magnesium alloy matrix. After grinding the ZK61M magnesium-zinc alloy workpiece or sample, wash it in ethanol and dry it. Among them, the magnesium alloy workpiece or sample is polished with a grinding wheel, for example, 120 mesh, 500 mesh, and 2000 mesh grinding wheels are used in sequence. Preferably, the sample is ultrasonically cleaned at 80-300W for no less than 1 hour. The drying temperature is 50°C and the drying time is no less than 1 hour.

[0031] Preparation of carbonate solution. Heat deionized water to 40-60°C, and then continuously introduce CO2 gas to obtain a carbonate solution; preferably, the flow rate of the CO2 gas is 0.5-1.5 L / min. The concentration of the carbonate solution is greater than 0.02 mol / L, and the pH is about 4.0. For example, take 1 L of deionized water, heat and stir to 50°C, introduce CO2 gas, control the flow rate of CO2 gas to be about 1 L / min, until the solution becomes weakly acidic, and prepare a carbonate solution. At this time, the pH value of the solution is about 4.0, and continue to pass CO2.

[0032] Preparation of magnesium-zinc layered double metal hydroxide anti-corrosion coating. The pretreated ZK61M magnesium-zinc alloy workpiece or sample is placed in a carbonate solution for the first immersion treatment; then, an alkaline solution is added thereto or the magnesium alloy substrate after the first immersion treatment is transferred to an alkaline solution for the second immersion treatment; the magnesium alloy substrate after the second immersion treatment is dried to obtain a magnesium-zinc layered double metal hydroxide anti-corrosion coating. During the preparation process, the magnesium-zinc layered double metal hydroxide can effectively block the contact between the corrosive medium and the metal, thereby having good anti-corrosion performance.

[0033] In an optional embodiment, the first immersion treatment is carried out under normal pressure; the temperature of the first immersion treatment is 20-50°C, preferably 50°C; the time of the first immersion treatment is more than 1 hour, preferably 1-4 hours, most preferably 1-2 hours.

[0034] In an optional embodiment, the alkaline solution comprises at least one of NaOH, KOH, LiOH, NH4OH, Ca(OH)2, Ba(OH)2, Sr(OH)2, CsOH, and FrOH. The pH value of the mixed solution after the alkaline solution is added dropwise and the pH value of the alkaline solution is greater than 8, preferably 9-12, and most preferably 10-11.

[0035] In an optional embodiment, the second immersion is carried out under normal pressure; the temperature of the second immersion is 30-90°C, preferably 90°C; the time of the second immersion is more than 1 hour, preferably 2-8 hours, most preferably 3-4 hours.

[0036] In an optional embodiment, preferably, the drying temperature is 40-60° C., preferably 50° C.; and the drying time is not less than 1 hour.

[0037] A transition layer solution is sprayed on the magnesium-zinc layered double metal hydroxide anti-corrosion coating formed in situ on the surface of the magnesium-zinc alloy substrate, and then dried in an oven to obtain a transition layer on the surface of the magnesium-zinc layered double metal hydroxide anti-corrosion coating. In the present invention, a transition layer is prepared on the surface of the magnesium-zinc layered double metal hydroxide anti-corrosion coating, which can, on the one hand, undergo ion replacement and chemical bonding with the magnesium-zinc layered double metal hydroxide anti-corrosion coating, and on the other hand, the transition layer can also bond with inorganic substances such as oxides and silicates of the inorganic thermal control coating to enhance the bonding force between the anti-corrosion coating and the thermal control coating.

[0038] In an optional embodiment, the transition layer solution is at least one of a silicate solution, a phosphate solution, a silica sol, an acrylic emulsion, tetraethyl orthosilicate, and a silane solution; preferably, the transition layer solution is at least one of a K2SiO4 solution, tetraethyl orthosilicate, an acrylic emulsion, and 3-aminopropyltriethoxysilane; the mass percentage concentration of the transition layer solution is 10% to 50%.

[0039] In an optional embodiment, the drying temperature is 30 to 120° C., and the drying time is 1 to 24 hours.

[0040] The thermal control coating is sprayed on the transition layer, dried in the shade and then placed in an oven to obtain an anti-corrosion thermal control dual-function coating on the surface of the magnesium alloy.

[0041] In an optional embodiment, the raw material composition of the thermal control coating is a mixture of ZnO powder, K2SiO4 solution and 3-aminopropyltriethoxysilane; preferably, the mass ratio of ZnO powder, K2SiO4 solution and 3-aminopropyltriethoxysilane is 0.1-1: 0.1-1: 0.1-1. If the mass ratio of ZnO powder, K2SiO4 solution and 3-aminopropyltriethoxysilane is not within this range, the thermal control coating cannot be prepared normally, if the mass of the powder exceeds the upper limit, the coating cannot be effectively formed, and if the mass of the binder exceeds the upper limit, the formed coating does not have fillers that effectively achieve thermal physical properties and does not have thermal control function.

[0042] The raw materials and composition used in the preparation of the thermal control coating of the present invention can ensure that the coating has a low solar absorption ratio, can be cured at a low temperature, and has good bonding performance with the magnesium-zinc layered double hydroxide anti-corrosion coating. In the preparation of the thermal control coating of the present invention, ZnO powder is used as a catalyst to promote the hydrolysis reaction of 3-aminopropyltriethoxysilane and the dehydration reaction of K2SiO4 solution to generate a cross-linked structure of silicon-oxygen bonds; at the same time, ZnO powder is used as a filler to provide a thermal control function for the coating, so that the coating has a low solar absorption ratio and a high infrared radiation rate.

[0043] In an optional embodiment, the drying temperature is 30 to 120° C., and the drying time is 0.5 to 12 hours.

[0044] In the present invention, the magnesium-zinc layered double metal hydroxide anti-corrosion coating and the thermal control coating interact with each other through chemical bonds to form an integrated coating, or the magnesium-zinc layered double metal hydroxide anti-corrosion coating and the transition layer and the transition layer and the thermal control coating interact with each other through chemical bonds to form an integrated coating, thereby realizing the preparation of the anti-corrosion and thermal control dual-functional composite coating.

[0045] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0046] Example 1 (1) A 20×20 mm ZK61M magnesium-zinc alloy (Zn content 5.43%) sample was polished with 120 mesh, 500 mesh, and 2000 mesh grinding wheels in sequence, ultrasonically cleaned in ethanol for 60 minutes, and then dried in a 50°C oven for 1 hour; (2) 1000 ml of deionized water was measured, heated and stirred to 50° C. CO2 gas was introduced, and the flow rate of CO2 gas was controlled to be about 1 L / min until the solution became weakly acidic to prepare a carbonate solution. At this time, the pH value of the solution was about 4.0, and CO2 was continuously introduced; (3) Soak the treated ZK61M magnesium-zinc alloy sample in a carbonic acid solution for 1 hour; (4) The immersed ZK61M magnesium-zinc alloy sample was transferred to a 50°C alkaline solution (solute: NaOH, 0.0001 mol / L) with a pH of 10 and immersed for 4 hours; (5) taking out the ZK61M magnesium-zinc alloy sample after immersion in the alkaline solution, drying it in an oven at 50° C. for 1 hour to obtain a magnesium-zinc layered double hydroxide anti-corrosion coating; (6) spraying K2SiO4 solution uniformly on the magnesium-zinc layered double hydroxide anti-corrosion coating on the surface of the magnesium alloy, drying in the shade and baking in an oven at 50°C for 6 hours to obtain a transition layer; (7) A mixture of ZnO powder, K2SiO4 solution and 3-aminopropyltriethoxysilane in a ratio of 1:0.5:0.5 was evenly sprayed on the transition layer, and after being dried in the shade, it was baked in an oven at 50°C for 1 hour to obtain an anti-corrosion and thermal control dual-function coating.

[0047] Example 2

[0048] The preparation process of the anti-corrosion and thermal control dual-function coating on the surface of the magnesium alloy in this Example 2 refers to that in Example 1, with the only difference being that the preparation of the transition layer in step (6) is not performed.

[0049] Example 3

[0050] The preparation process of the anti-corrosion and thermal control dual-function coating on the surface of the magnesium alloy in this Example 3 refers to that in Example 1, with the only difference being that in step (6), the K2SiO4 solution is replaced with tetraethyl orthosilicate.

[0051] Example 4

[0052] The preparation process of the anti-corrosion and thermal control dual-function coating on the surface of the magnesium alloy in this Example 4 refers to that in Example 1, with the only difference being that in step (6), the K2SiO4 solution is replaced with an acrylic emulsion.

[0053] Example 5

[0054] The preparation process of the anti-corrosion and thermal control dual-function coating on the surface of the magnesium alloy in this Example 5 refers to that in Example 1, with the only difference being that in step (6), the K2SiO4 solution is replaced with 3-aminopropyltriethoxysilane.

[0055] Example 6

[0056] The preparation process of the anti-corrosion and thermal control dual-function coating on the surface of the magnesium alloy in this Example 6 refers to that in Example 1, with the only difference being that in step (7), the ratio of ZnO powder, K2SiO4 solution and 3-aminopropyltriethoxysilane is 1:1:1.

[0057] Example 7

[0058] The preparation process of the anti-corrosion and thermal control dual-function coating on the surface of the magnesium alloy in this Example 7 refers to that in Example 1, with the only difference being that in step (7), the ratio of ZnO powder, K2SiO4 solution and 3-aminopropyltriethoxysilane is 1:1:0.5.

[0059] Example 8

[0060] The preparation process of the anti-corrosion and thermal control dual-function coating on the surface of the magnesium alloy in this Example 8 refers to that in Example 1, with the only difference being that in step (7), the ratio of ZnO powder, K2SiO4 solution and 3-aminopropyltriethoxysilane is 0.5:1:1.

[0061] Comparative Example 1

[0062] In this comparative example 1, the thermal control coating is directly sprayed on the surface of the ZK61M magnesium-zinc alloy: a mixture of ZnO powder, K2SiO4 solution and 3-aminopropyltriethoxysilane in a ratio of 1:0.5:0.5 is evenly sprayed on the surface of the ZK61M magnesium-zinc alloy, and then dried in a 50°C oven for 1 hour.

[0063] Comparative Example 2

[0064] The preparation process of the anti-corrosion and thermal control dual-function coating on the surface of the magnesium alloy in Comparative Example 2 refers to that in Example 1, with the only difference being that in step (7), the ratio of ZnO powder to water is 1:1.

[0065] Comparative Example 3

[0066] The preparation process of the anti-corrosion and thermal control dual-function coating on the surface of the magnesium alloy in this comparative example 3 refers to that in Example 1, with the only difference being that in step (7), the ratio of ZnO powder, K2SiO4 solution and 3-aminopropyltriethoxysilane is 0.95:0.02:0.03.

[0067] Comparative Example 4

[0068] The preparation process of the anti-corrosion and thermal control dual-function coating on the surface of the magnesium alloy in this comparative example 4 refers to that in Example 1, with the only difference being that in step (7), the ratio of K2SiO4 solution to 3-aminopropyltriethoxysilane is 1:1.

[0069] Table 1 lists the types of transition layers, composition ratios of thermal control layer raw materials, macroscopic appearance, corrosion performance and thermal control performance (solar absorption ratio) of Examples 1-8 and Comparative Examples 1-4.

[0070] Table 1:

[0071] As shown in Table 1, the anti-corrosion and thermal control dual-function coating designed by the present invention can be successfully prepared on the surface of the magnesium alloy. The corrosion potential of the anti-corrosion and thermal control dual-function coating of the present invention is significantly higher than the corrosion potential of the magnesium alloy -1.4645 eV, and has a good anti-corrosion effect. In the case where the anti-corrosion coating is not prepared, the thermal control coating cannot be prepared on the surface of the magnesium alloy in Comparative Example 1. After the thermal control coating is sprayed, the magnesium alloy surface has severe corrosion phenomena (such as Figure 3 As shown), there is basically no bonding force between the thermal control coating and the substrate. Comparative Examples 1, 7, 8 and Comparative Example 4 show that the increase of ZnO powder in the thermal control coating can effectively reduce the solar absorption ratio of the coating. Comparative Example 1 and Comparative Example 2 show that adding K2SiO4 solution and 3-aminopropyltriethoxysilane to the thermal control coating will effectively form a thermal control coating. Comparative Example 1 and Comparative Example 3 show that controlling the raw material composition of the thermal control coating within a suitable range will effectively form a thermal control coating.

[0072] Figure 1 It is a schematic diagram of an anti-corrosion thermal control dual-function coating. As can be seen from the figure, the coating provided by the present invention is composed of a two-layer structure of an anti-corrosion coating (transition layer) and a thermal control coating.

[0073] Figure 2 This is the anti-corrosion thermal control dual-function coating prepared in Example 1. As can be seen from the figure, the inorganic thermal control coating can be successfully prepared on the surface of the magnesium alloy by using the present invention.

Claims

1. A corrosion-resistant and thermal-control dual-function coating on the surface of a magnesium alloy, characterized in that: include: A magnesium-zinc alloy substrate, an anti-corrosion coating formed in situ on the surface of the magnesium-zinc alloy substrate, and a thermal control coating dispersed on the surface of the anti-corrosion coating; preferably, the anti-corrosion coating is a magnesium-zinc layered double metal hydroxide coating; and the thermal control coating is an inorganic thermal control coating.

2. The anti-corrosion and thermal control dual-function coating on the surface of magnesium alloy according to claim 1, characterized in that: The content of Zn in the magnesium-zinc alloy matrix is ​​2-9 mol%, and the balance is Mg; The inorganic thermal control coating is at least one of a silicate coating, a phosphate coating, a silica sol coating, and an oxide coating.

3. The anti-corrosion and thermal control dual-function coating on the surface of magnesium alloy according to claim 1 or 2, characterized in that: The surface of the anti-corrosion coating also includes a transition layer; preferably, the transition layer is at least one of a silicate solution coating, a phosphate solution coating, a silica sol coating, an acrylic emulsion coating, a tetraethyl orthosilicate coating, and a silane solution coating.

4. The anti-corrosion and thermal control dual-function coating on the surface of a magnesium alloy according to any one of claims 1 to 3, characterized in that: The thickness of the anti-corrosion and thermal control dual-function coating is 100 to 200 μm; The corrosion potential of the anti-corrosion and thermal control dual-function coating is greater than -1.4645 eV.

5. A method for preparing an anti-corrosion and thermal control dual-function coating on the surface of a magnesium alloy according to any one of claims 1 to 4, characterized in that: include: (1) forming an anti-corrosion coating of magnesium-zinc layered double hydroxide in situ on the surface of magnesium-zinc alloy substrate; (2) Spraying a thermal control coating on the magnesium-zinc layered double metal hydroxide anti-corrosion coating, and drying the coating to obtain an anti-corrosion and thermal control dual-function coating on the surface of the magnesium alloy.

6. The preparation method according to claim 5, characterized in that: In step (1), the preparation method of the magnesium-zinc layered double metal hydroxide anti-corrosion coating comprises: placing a magnesium alloy substrate in a carbonate solution for a first immersion treatment; then, adding an alkaline solution thereto or transferring the magnesium alloy substrate after the first immersion treatment to an alkaline solution for a second immersion treatment; and drying the magnesium alloy substrate after the second immersion treatment to obtain a magnesium-zinc layered double metal hydroxide anti-corrosion coating.

7. The preparation method according to claim 6, characterized in that: The concentration of the carbonate solution is greater than 0.02 mol / L, and the pH is not higher than 5.0; preferably, the pH is 3.8 to 4.2; The preparation process of the carbonate solution is: heating deionized water to 40-60° C., and then continuously introducing CO 2 gas to obtain a carbonate solution; preferably, the flow rate of the introduced CO 2 gas is 0.5-1.5 L / min.

8. The preparation method according to claim 6, characterized in that: The first soaking treatment is carried out under normal pressure; the temperature of the first soaking treatment is 20-50°C, preferably 50°C; the time of the first soaking treatment is more than 1 hour, preferably 1-4 hours, and most preferably 1-2 hours; The alkaline solution comprises at least one of NaOH, KOH, LiOH, NH4OH, Ca(OH)2, Ba(OH)2, Sr(OH)2, CsOH, and FrOH; The pH value of the mixed solution after the alkaline solution is added is greater than 8, preferably 9 to 12, and most preferably 10 to 11; The second soaking is carried out under normal pressure; the temperature of the second soaking is 30 to 90° C., preferably 90° C.; the time of the second soaking is more than 1 hour, preferably 2 to 8 hours, and most preferably 3 to 4 hours; The drying temperature is 40-60° C., preferably 50° C.; the drying time is not less than 1 hour.

9. The preparation method according to claim 5, characterized in that: The preparation method further comprises: before spraying the thermal control coating on the magnesium-zinc layered double metal hydroxide anti-corrosion coating, spraying a transition layer solution on the magnesium-zinc layered double metal hydroxide anti-corrosion coating, and after drying, obtaining a transition layer on the surface of the magnesium-zinc layered double metal hydroxide anti-corrosion coating; Wherein, the transition layer solution is at least one of a silicate solution, a phosphate solution, a silica sol, an acrylic emulsion, tetraethyl orthosilicate, and a silane solution; preferably, the transition layer solution is at least one of a K2SiO4 solution, tetraethyl orthosilicate, an acrylic emulsion, and 3-aminopropyltriethoxysilane; the mass percentage concentration of the transition layer solution is 10% to 50%; The drying temperature is 30 to 120° C. and the drying time is 1 to 24 hours.

10. The preparation method according to claim 5, characterized in that: In step (2), the raw material composition of the thermal control coating is a mixture of ZnO powder, K2SiO4 solution and 3-aminopropyltriethoxysilane; preferably, the mass ratio of ZnO powder, K2SiO4 solution and 3-aminopropyltriethoxysilane is 0.1-1:0.1-1:0.1-1; The drying temperature is 30-120° C. and the drying time is 0.5-12 hours.